2003
DOI: 10.1148/radiol.2262011450
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of a US Contrast Agent in Benign and Malignant Adnexal Tumors

Abstract: After microbubble contrast agent injection, malignant and benign adnexal lesions behave differently in degree, onset, and duration of Doppler US enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 29 publications
6
68
1
3
Order By: Relevance
“…In the first study, enhancement ratio, uptake time, and wash-out parameters were excellent for discriminating benign from malignant ovarian tumors in women. 6 In the second study, the wash-out time and AUC were shown to be more accurate than Doppler sonography for discrimination of ovarian cancer from benign tumors. 7 Characterization of ovarian lesions may be improved with new imaging modalities such as PIH sonography.…”
Section: D a Bmentioning
confidence: 91%
See 1 more Smart Citation
“…In the first study, enhancement ratio, uptake time, and wash-out parameters were excellent for discriminating benign from malignant ovarian tumors in women. 6 In the second study, the wash-out time and AUC were shown to be more accurate than Doppler sonography for discrimination of ovarian cancer from benign tumors. 7 Characterization of ovarian lesions may be improved with new imaging modalities such as PIH sonography.…”
Section: D a Bmentioning
confidence: 91%
“…4,5 A few studies have evaluated the use of contrastenhanced TVS in the differentiation of benign and malignant ovarian tumors by showing more prominent enhancement of malignant lesions. [6][7][8][9][10] However, some of these studies were performed with Doppler imaging to assess tumor enhancement after contrast agent administration. 7,8 This method has low contrast and resolution, substantial background noise, and considerable operator dependence.…”
mentioning
confidence: 99%
“…Harmonics and pulse inversion technology have improved signal-to-noise ratios and structural conspicuity while the introduction of IV contrast agents (akin to those used with CT and MRI) has helped to more accurately detect, characterize and quantify aberrant vascularity and blood flow. [82][83][84] The contrast enhancement of ultrasound helps to visualize tumor neovascularization in developing microscopic (not macroscopic) tumors by delineating the aberrant leaky vascular channels associated with early malignancy. The incompetent extracellular matrix of neovascularization allows extravasation of RBCs (5-7 microns) and contrast agents (1-10 microns in diameter), which can then be detected by ultrasound.…”
Section: Epigenetic Aberrations As Biomarkers In Eocmentioning
confidence: 99%
“…However, magnetic resonance imaging (MRI) is superior in the characterization of adnexal masses (4) and should be used to further characterize indeterminate adnexal mass identified by US (5). Previous imaging studies have reported accuracies in the characterization of malignancy of adnexal masses ranging from 60 to 95% for US (4,6,7) and from 83 to 94% for MRI (3, 4, 7Á13); the lower figure of 83% is from a relatively early pioneer study using older equipment (3).…”
mentioning
confidence: 99%